(untitled) (International Educators Conference, 2025)
This scientific research discusses the organizational and methodological aspects of accounting for fixed assets in budgetary institutions. It highlights the nature of fixed assets, their practical aspects, and the objectives set for accounting. The role and importance of inventory in the organization of fixed asset accounting in budgetary institutions are scientifically substantiated.